PENGARUH PERENCANAAN PAJAK, ASIMETRI INFORMASI DAN BEBAN PAJAK TANGGUHAN TERHADAP MANAJEMEN LABA (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia Periode 2016-2018) - Imelda Yofa Aprillia; Abdul Wahid Mahsuni; M. Cholid Mawardi (e_Jurnal Ilmiah Riset Akuntansi, 2020)
This study aims to determine and analyze the impact of tax planning, information asymmetry, and the deferred tax expense on earnings management in manufacturing companies listed in Indonesia Stock Exchange 2016-2018 period. The data analysis method used is linear regression analysis regression. Sampling using purposive sampling method and acquired 18 companies out of 148 companies manufacturing in accordance with the criteria that will be used as a research object. Based on the research, it is known that tax planning, information asymmetry, and the deferred tax expense simultaneously influence significantly to earnings management in companies listed on the Stock Exchange Indonesia in the period 2016 - 2018. However, partial, tax planning and significant positive effect on earnings management. Asymmetry of information is partially affected positively and significantly to earnings management. While the deferred tax expense is partially affected negatively to earnings management. With the value of R Square (R2) of 66.5% which is where the dependent variable is affected by the independent variable. As well as the dependent variable remaining 33.5% influenced by other variables that are not addressed in this study. Keywords: Tax Planning, Information Asymmetry, Deferred Tax Expense, Earnings Management